Difficult Clients: Who Are They and How Do We Help Them? - Seligman, Linda; Gaaserud, Lynn (Canadian Journal of Counselling and Psychotherapy, 2007)
A review of the literature on dealing with resistant clients is presented. Based on this review, the authors developed a survey designed to elicit counsellors' reactions to and experiences with resistant clients. Responses received from 215 members of the American Mental Health Counselors Association suggest that nearly all counsellors have encountered resistant clients, but the counsellors' reactions to and methods of dealing with these clients differ considerably.